Global Matrix of 2022 Para Report Cards on Physical Activity of Children and Adolescents With Disabilities (Adapted Physical Activity Quarterly, 2023)
Sonderheft zum Thema "Global Matrix of 2022 Para Report Cards on Physical Activity of Children and Adolescents With Disabilities".